THE ANALYSIS OF STUDENTS’ BARRIERS IN TRANSLATING THE DAILY INDONESIAN-ENGLISH EXPRESSION AT MA AS’ADIYAH PUTRI SENGKANG - Agustiani Khaeruddin; Muhammad Yaumi (Universitas Islam Negeri Alauddin Makassar, 2016)
This research was aimed to identify the second grade students of MA As’adiyah Sengkang’s barriers in translating Indonesian–English questions of daily expression, factors affecting the barriers, and strategies to solve them. The data were analyzed by using the qualitative descriptive method. The instruments used were Forum Group Discussion (FGD), interview, and observation. The research informants were the second grade students of Ilmu Agama Islam (IAI) department at MA As’adiyah Putri Sengkang. The result of the research showed that some barriers that the students encountered were barriers in word ordering, grammar, the use of pronoun, the use of idiom, and lack of vocabulary. The barriers occurred because of some factors affecting, such as limited learning media, lack of English book references, limited English learning (only at school), lack of interest in both the English material and the teacher’s teaching method, and the differences of students’ ability in understanding English learning. Some strategies that the students did in solving the barriers were using a dictionary, using google translate, learning grammar from a book, asking the teacher or asking the other friends, learning English from the movies and songs, accessing Internet to learn in the Internet stall, and taking a course.